Primitive Neuroectodermal Tumor of the Liver: A Case Report - Eduardo Cambruzzi; Enilde Eloena Guerra; Hamilton Cardoso Hilgert; Herbert Jorge Schmitz; Vinícius Lopes Silva; Daniel Marini Milani; Ricardo Pedrini Cruz; Raul Pruinelli (Case Reports in Medicine)
Primary liver sarcomas represent a rare group of neoplasias, with angiosarcoma being the most common histological type. Primitive neuroectodermal tumor (PNET) represents a high malignant neoplasia that usually affects the central nervous system and soft tissues. An 18-year-old male patient was admitted with clinical complains of pain in the right upper abdominal quadrant. The clinical evaluation revealed a solid mass in the right hepatic lobe. On the gross examination of the resected liver specimen, the right lobe of the liver was replaced by a yellow-red solid mass measuring 21 cm in its largest dimension. On the histopathology, a tumor composed of small round blue cells with little cytoplasm and round nuclei was identified. The lesion revealed positive immunoexpression for vimentin and CD99 and negative immunostaining for desmin, CD45, cytokeratin, and neuroblastoma protein, suggesting, then, the diagnosis of PNET. Although it is an unusual tumor, it should be considered in the differential diagnosis of liver masses, especially in young patients.